Basic concepts of an open distributed system for cooperative design and structure analysis - Krok, Józef; Leżański, Pawel; Orkisz, Janusz; Przybylski, Przemysław; Schaefer, Robert (Computer Assisted Methods in Engineering and Science, 2023)
Distributed programming paradigm in key stages of CAD process is proposed, as an alternative to the conventional single-computer-single-user approach. Object-oriented technology is suggested for cooperative design and implementation of large scale engineering computations. Complex ideas concerning specification and design of the new system are presented. In addition, an example of the transformation of the old CAD system to the new environment is described.